Properties of Attractive Points in CAT(0) Spaces: K. Kunwai, A. Kaewkhao, W. Inthakon - Team, Support (Thai Journal of Mathematics, 2015)
We study attractive points of nonlinear mappings in CAT(0) spaces. We prove the attractive point theorem for normally generalized hybrid mappings in a CAT(0) space satisfying (S) property.